2017
DOI: 10.14745/ccdr.v43i12a05
|View full text |Cite
|
Sign up to set email alerts
|

Setting the stage for expanding HIV pre-exposure prophylaxis use in Canada

Abstract: Human immunodeficiency virus (HIV) infection continues to disproportionately affect vulnerable populations in Canada; particularly men who have sex with men (MSM). Novel HIV prevention strategies have recently expanded from the use of non-occupational post-exposure prophylaxis (nPEP) after high risk exposures to the use of pre-exposure prophylaxis (PrEP) in which individuals reduce risk of HIV infection through use of combination antiretrovirals taken prior to risk exposure. With approval of tenofovir/emtricit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…In most settings in Canada, PrEP is prescribed primarily by HIV or sexual health specialists, however there are no restrictions for general practitioners to prescribe PrEP 13. Public reimbursement of PrEP varies provincially across Canada.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most settings in Canada, PrEP is prescribed primarily by HIV or sexual health specialists, however there are no restrictions for general practitioners to prescribe PrEP 13. Public reimbursement of PrEP varies provincially across Canada.…”
Section: Introductionmentioning
confidence: 99%
“…In Quebec, TDF-FTC is reimbursable through the provincial drug plan without restriction by HIV status, thereby permitting off-label dispensing to PrEP users since 2013 with a monthly copayment ($80–90 CAD) or via private insurance. Elsewhere in Canada, TDF-FTC for use as PrEP was not reimbursable until after 2017,13 and therefore was largely inaccessible due to prohibitive out-of-pocket costs ranging from $800 to 1000 CAD for a monthly course of daily PrEP 14. This issue of cost as a barrier to PrEP access was addressed in a 2016 report by the Canadian Drug Expert Committee of the Canadian Agency for Drugs and Technologies in Health recommending that the cost of PrEP be subsidised by public drug plans in Canada 15…”
Section: Introductionmentioning
confidence: 99%
“… 2 Several experts have recognized that the end of the HIV epidemic would need to include prescription of PrEP by a wider range of health care providers. 6 , 29–32 …”
Section: Discussionmentioning
confidence: 99%
“…26 However, surveys have shown that providers feel that it lies within their scope of practice, and that primary care is an appropriate setting for this aspect of HIV care. 2729 A study done using a Project ECHO telehealth program to deliver PrEP education showed that providers reported improved knowledge about, and increased likelihood of providing, PrEP. 30…”
Section: Discussionmentioning
confidence: 99%